Diagnostic Yield and Clinical Impact of Video Capsule Endoscopy in Patients with Chronic Diarrhea: A Korean Multicenter CAPENTRY Study - Song, Hyun Joo; Moon, Jeong Seop; Jeon, Seong Ran; Kim, Jin-Oh; Kim, Jinsu; Cheung, Dae Young; Choi, Myung-Gyu; Lim, Yun Jeong; Shim, Ki-Nam; Ye, Byong Duk; Cheon, Jae Hee; Park, Cheol Hee; et al. (Gut and liver, 2017)
In some cases, chronic diarrhea is unexplained, and small bowel disorders may be one of the causes. The aim of this study was to assess the diagnostic yield and clinical impact of video capsule endoscopy (VCE) in patients with chronic diarrhea. We retrospectively analyzed records from October 2002 to August 2013 in the VCE nationwide database registry (n=2,964). Ninety-one patients from 15 medical centers (60 males and 31 females; mean age, 47±19 years) were evaluated for VCE as a result of chronic diarrhea. The duration of chronic diarrhea was 8.3±14.7 months. The positive diagnostic yield of VCE was 42.9% (39/91). However, 15.4% (14/91) exhibited an inconsistent result, and 41.8% (38/91) were negative. Abnormal findings consistent with chronic diarrhea included erosions/aphthous ulcers (19.8%), ulcers (17.6%), mucosal erythema (3.3%), edema (1.1%), and luminal narrowing (1.1%). The most common diagnoses were functional diarrhea associated with irritable bowel syndrome in 37 patients (40.7%) and Crohn's disease in 18 patients (19.8%). After VCE examination, the diagnosis was changed in 34.1% of the patients (31/91). Hematochezia (odds ratio [OR], 8.802; 95% confidence interval [CI], 2.126 to 36.441) and hypoalbuminemia (OR, 4.811; 95% CI, 1.241 to 18.655) are predictive factors of a positive diagnostic yield. VCE had a favorable diagnostic yield and clinical impact on the management of patients with chronic diarrhea.